Social Philosophical Concepts, Methodology and Gnoseological Aspects of the Study of the Phenomenon of Poverty - Zakirjan, Suyarov (Research Parks Publishers, 2023)
this article presents a number of problems and challenges that threaten its progress before humanity in the present time, when strong global changes are taking place rapidly in the world. Along with climate change, desertification, environmental pollution and a number of other natural and man-made factors, economic and various social problems are also manifested as negative manifestations of today's globalization processes.